Canscorinella deccanensis (Gentianaceae: Canscorinae), a new species from Maharashtra, India - Kambale, Sharad Suresh; Sardesai, Milind Madhav (Phytotaxa, 2020)
Members of the family Gentianaceae Jussieu (1789: 141) (Gentianales) are of economic importance and utilized for the several ailments (Bhandari et al. 2006). Thiv and Kadereit (2002) after cladistic analysis of the evolution of anisomorphic androecia in the subtribe Canscorinae proved the monophyly of the Canscora Lamarck (1785: 601). Canscorinella Shahina & Nampy (2014: 219), a recently described genus, based on the isomorphy of the stamens, is represented by only two species in India viz., C. bhatiana (K.S. Prasad & Raveendran 2012: 197) Shahina & Nampy (2014: 219) and C. stricta (Sedgwick 1921: 126) Nampy & Shahina (2014: 221) and so far known only from Western Ghats of Kerala and Karnataka, respectively.